Geopolitical risk, economic policy uncertainty, and bank stability in BRICS countries - Oluwaseyi Ebenezer Olalere; Janine Mukuddem-Petersen (Cogent Economics & Finance, 2024)
Global tensions and uncertainty in economic policy can cause structural change and disruption in the volatile sector of the economy. This study investigates the effects of geopolitical risk on bank stability and the role of economic policy uncertainty in this relationship in BRICS countries. We use the panel VAR and the two-step System GMM estimation technique. The study uses bank-level data from 105 commercial banks during 2009-2021, totaling 1,365 observations. The empirical results revealed that increased geopolitical risk and economic policy uncertainty reduce bank stability once other traditional drivers are controlled for. We found that geopolitical events tend to adversely influence the stability of banks. The results also reveal that the interaction between economic policy uncertainty and geopolitical risk has a negative significant impact on bank stability. More importantly, our findings are robust and offer critical policy interventions and implications for managers, policymakers, and investors in emerging markets.
Keywords: 330; bank stability; geopolitical risk; economic policy uncertainty; panel VAR; GMM estimate